Corporate governance matters : a closer look at organizational choices and their consequences - Larcker, David; Tayan, Brian , 1975- (FT Press, 2011)
The complete, up-to-date corporate governance reference for every board member, officer, director, and stakeholder.??Brings together crucial knowledge, new academic research, and a complete decisionmaking framework.?Objectively and fully addresses every component of governance, with no axe to grind: explains what's known and what isn't, helping leaders make better choices in the face of uncertainty.?By David Larcker, director of Stanford's highly influential Corporate Governance Research Program.Corporate Governance Matters gives corporate board members, officers, directors, and other stakeholders the full spectrum of knowledge they need to implement and sustain superior governance. Authored by two leading experts, this comprehensive reference thoroughly addresses every component of governance. The authors carefully synthesize current academic and professional research, summarizing what is known, what is unknown, and where the evidence remains inconclusive. Along the way, they illuminate many key topics overlooked in previous books on the subject. Coverage includes:??International corporate governance.?Compensation, equity ownership, incentives, and the labor market for CEOs.?Optimal board structure, tradeoffs, and consequences.?Governance, organizational strategy, business models, and risk management?Succession planning.?Financial reporting and external audit.?The market for corporate control.?Roles of institutional and activist shareholders.?Governance ratings The authors offer models and frameworks demonstrating how the components of governance fit together, with concrete examples illustrating key points. Throughout, their balanced approach is focused strictly on two goals: to 'get the story straight,' and to provide useful tools for making better, more informed decisions